Unfolding women’s role in small-scale fishing community in The Philippines toward formulating a gender-sensitive local government policy - Joy Tricia Mae Corpuz; Ma. Shiela Simat; Maria Gracia Samson; Brenda Villamor; Reynald Cacho (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
Women have a crucial role in the fishery value chains, from pre-fishing to post-fishing activities; however, the lack of sex-disaggregated local level data aggravates the women’s invisibility and marginalization in the informal fishing industry and community. Generating local knowledge and representation, this study presents women’s role and challenges working in small-scale fisheries in Perez, Quezon, Philippines. Fifty female fisherfolks from the said sector participated in this case study. The results from the field survey indicate that the participants widely dispersed to inland capture fisheries, marine capture fisheries, non-food use production and food fishery production categories. The results also showed that the respondents are scattered across the value chain: active fishing, processing, subsistence fishing, marketing, and pre-fishing activities, in varying intensity and pattern. In contrast to stereotypes that exclusively associate women to gleaning invertebrates, the majority target fish species and other marine invertebrates. Environmental, socio-economic, personal and gender factors are the common constraints that limit their productivity, output, and more importantly their equitable roles and identities. Although coming from a small fishing community, the findings of this study may provide baseline information for relevant local government agency to further intensify profiling on the grounds and to strategically implement gender-sensitive mainstreaming programs.